A Scoring Index of Prioritization Factors Between Patients: An Iberian Comparison. Issue 3 (July 2019) - Pinho, Micaela; Borges, Ana Pinto
Abstract : This study intends to develop a Prioritization Scoring Index of Iberian Peninsula comprising Portuguese and Spanish citizens, to weigh the importance assigned to rationing criteria used to prioritize patients. Data were collected through an online survey from 2 samples of 355 Portuguese and 564 Spanish members of the general public. Respondents faced 12 hypothetical rationing scenarios and should reveal their level of agreement with each one according to a Likert scale. The statements comprise 3 allocative considerations: egalitarianism, efficiency, and equity. Findings suggest that Portuguese and Spanish respondents gave greater importance to the treatments outcomes, to the severity of the illness, and to younger patients. Furthermore, Iberian respondents assigned 57% of the weighting to equity considerations, 40% to efficiency considerations, and approximately only 3% to egalitarianism. Spaniards weighted more than Portuguese both equity and efficiency considerations while weighted less the egalitarian principle. Iberian Peninsula respondents require resource allocation decisions in health to be informed by considerations of equity as well as efficiency. As the first was most valued, it seems plausible that Portuguese and Spanish respondents are willing to sacrifice some efficiency to achieve a more equitable distribution of health.